Adsorption of perchlorate from water using quaternary ammonium‐functionalized chitosan beads. Issue 2 (8th August 2019) - Sowmya, Appunni; Das, Debanjani; Prabhakar, Sivaraman; Kumar, Marichamy Magesh; Anbalagan, Kumaraguru; Rajesh, Mathur
Abstract: Perchlorate, one of the persistent inorganic pollutants, was efficiently removed from water using quaternary ammonium‐functionalized cross‐linked chitosan beads (QACB). This synthesized bead was found to be efficient in terms of perchlorate removal capacity, 100% regeneration of used beads (using HCl or NaCl) and selectivity in the presence of coanions, namely, chloride, sulfate, carbonate, and nitrate. QACB removes perchlorate by exchange of chloride ions. QACB was able to remove >95% perchlorate from brackish water. Batch studies were carried out in order to optimize the condition for maximum perchlorate removal. The perchlorate removal capacity of QACB from 1, 000 mg/L of aqueous solutions was 153.0 mg/g. The outcome of pH variation studies indicated that QACB is able to remove perchlorate in the pH ranges of 2–11. Equilibrium isotherm data of adsorption of perchlorate at temperature 303, 313, and 323 K were well fitted to the linear Freundlich, Langmuir, and Dubinin–Radushkevich isotherm models. The adsorption kinetics data were best described by the pseudo‐second‐order kinetic model. FTIR was used to confirm the interaction of perchlorate with QACB. A small‐scale column test was carried out to evaluate the capacity of QACB for removing perchlorate from brackish water.